Arabic Language Learning Motivation Among Non-Native Learners: A Systematic Literature Review (2020–2026) - Anyes Lathifatul Insaniyah; Yeniati Ulfah (SIMFONI: Jurnal Sains dan Sosial Multidisipliner, 2026)
Motivation is a crucial driver for the sustained learning of Arabic among non-native speakers; however, the construct is simultaneously influenced by religious goals, identity, integrativeness, self-efficacy, the learning environment, and instructional design. This article aims to map motivational orientations, personal and contextual factors, pedagogical strategies, and sources of demotivation based on research conducted between 2020 and 2026. The review adapts PRISMA 2020 principles to analyze a verified corpus of 32 sources. Six books serve as the theoretical and methodological foundation, one secondary review article acts as a point of comparison, and 25 journal articles are included in the thematic synthesis. The results reveal four primary patterns. First, religious-spiritual motivation is a strong distinguishing characteristic, particularly among Muslim learners. Second, identity, integrativeness, autonomy, metacognition, self-efficacy, and learning strategies interact dynamically with learning outcomes. Third, supportive environments, teacher competence, curriculum relevance, social interaction, and classroom experiences shape the quality of motivation. Fourth, collaborative learning and digital media—such as LMS, gamification, game-based learning, Instagram, dubbing, and CIRC—tend to enhance attention, engagement, self-confidence, and satisfaction, whereas infrastructure barriers, monotonous methods, limited interaction, and linguistic difficulties trigger demotivation. This study proposes an integrative model of motivation that positions the learner as an individual within a specific context and recommends longitudinal, cross-level, and cross-cultural research utilizing validated instruments.